2017
DOI: 10.1111/are.13300
|View full text |Cite
|
Sign up to set email alerts
|

Effects ofBacillus subtilisstrains and the prebiotic Previda®on growth, immune parameters and susceptibility toAeromonas hydrophilainfection in Nile tilapia,Oreochromis niloticus

Abstract: This study was conducted to evaluate the individual and combined effects of long-term feeding of diets containing two probiotic Bacillus subtilis group strains (Aqua NZ and AP193) and the prebiotic Previda â , a commercial hemicellulose extract, on growth performance, immune parameters and Aeromonas hydrophila susceptibility of juvenile Nile tilapia, Oreochromis niloticus. Nile tilapia of average weight 7.47 AE 0.11 g were fed diets formulated with the probiotics and/or the prebiotic, or a control diet for 8 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 54 publications
2
27
1
Order By: Relevance
“…In this work, no significant differences in fish survival between treatments were observed, but Addo et al (2017) observed a significant effect of the addition of probiotic B. subtilis on feeding (for 56 days) on the survival of Nile tilapia after challenge of oral infection with Aeromonas hydrophila. The effect of probiotics on the host is also related to feeding time and the type of stress caused.…”
Section: Discussioncontrasting
confidence: 47%
See 1 more Smart Citation
“…In this work, no significant differences in fish survival between treatments were observed, but Addo et al (2017) observed a significant effect of the addition of probiotic B. subtilis on feeding (for 56 days) on the survival of Nile tilapia after challenge of oral infection with Aeromonas hydrophila. The effect of probiotics on the host is also related to feeding time and the type of stress caused.…”
Section: Discussioncontrasting
confidence: 47%
“…count, in which probiotic treatments in the feed and control displayed lower results than the probiotic treatment in water. The effect of probiotics on growth performance in tilapia and other fish may be related to different interactions between probiotics, intestinal microbiota and host (Addo et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Addo et al. () found no statistical difference in the zootechnical parameters of O. niloticus after 8 weeks of feeding with diet containing Bacillus subtilis supplemented, or not, with Previda ® prebiotic.…”
Section: Discussionmentioning
confidence: 98%
“…Among the microorganisms used for this purpose, lactic acid bacteria are gram‐positive enterobacteria that produce lactic acid as the main product of their fermentation (Calo‐Mata et al., ). In recent years, several studies have demonstrated the ability of probiotics to improve the immune system of animals, especially when applied during the early stages of development (Addo et al., ; Dawood et al., ; Jatobá & Mouriño, ; Jatobá et al., ; Pereira et al., ; Pourgholam, Khara, Safari, Sadati, & Aramli, ).…”
Section: Introductionmentioning
confidence: 99%
“…In the past decade, interest in the use of probiotics for modulation of the non-specific immune system of fish against diseases has been increasing [19][20][21][22][23][24]. Dietary administration of bakers' yeast, Saccharomyces cerevisiae and Bacillus subtilis have been used to improve immune response in different species of fish [21,[23][24][25][26][27][28][29][30][31]. However, despite these studies, it is still worth noting that the application of probiotics in low input ponds remain unknown yet their effects could be more striking in poor conditions exhibited in low input ponds [32].…”
Section: Introductionmentioning
confidence: 99%